НАЦИОНАЛЬНО-ТЕРРИТОРИАЛЬНОЕ РАЗМЕЖЕВАНИЕ В СРЕДНЕЙ АЗИИ И КАЗАХСТАНЕ В 1924 ГОДУ (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The national-territorial demarcation of Central Asia in 1924-1925 was a turning point in the history of the region. The political and ideological transformations of the Soviet period, provoked by the revolutionary events, created prerequisites for the formation of new state formations aimed at eliminating interethnic discord and supporting socialist construction. At the same time, deep ethnic and territorial contradictions emerged due to the complex interaction of pan-Turkist ideas, colonial heritage and local traditions. The results of the reforms had a lasting impact on the economic and cultural life of the peoples of the region, determining the modern structure of the national states of Central Asia.
Keywords: Central Asia, Pan-Turkism, demarcation, USSR, ethnic contradictions